PSYCHOLOGICAL STRATEGIES FOR THE PREVENTION AND OVERCOMING OF PROFESSIONAL BURNOUT AMONG UNIVERSITY TEACHERS (Psychology Travelogs, 2025)
The article presents an extended theoretical analysis of professional burnout among university teachers as a complex psychological, emotional and social phenomenon. The concept of burnout is discussed through classical and modern scientific approaches, which emphasize its gradual development and multidimensional structure. Professional burnout is defined as a state of emotional exhaustion, depersonalization, decreased motivation and a reduction of personal professional effectiveness that arise under conditions of chronic stress and prolonged pedagogical overload. Historical interpretations and well-known theoretical models describe burnout as a dynamic process influenced by both individual and organizational determinants, making it especially relevant in academic settings.A detailed review of psychological factors contributing to burnout is provided. Among the most significant are chronic fatigue, emotional pressure, scarcity of personal time, conflicts with students or colleagues, perfectionism, reduced self-esteem, difficulties in self-regulation and ineffective coping strategies. These factors create a cumulative effect that leads to emotional disengagement, irritability, psychosomatic reactions and withdrawal from professional duties. Manifestations of burnout in higher education include professional indifference, loss of pedagogical enthusiasm, impaired communication, lowering of teaching quality and dissatisfaction with academic results.The article also presents effective strategies for prevention and correction. Individual measures include the development of emotional intelligence, self-reflection, stress management skills, cognitive restructuring and support of inner psychological resources. Organizational measures emphasize the need for supervisory support, and psychological counseling.
Keywords: professional burnout; university teachers; perfectionism; self-esteem; psycho-emotional state; prevention; psychological intervention; psychological counseling